A Phase II Study of Ifosfamide, Methotrexate, Etoposide, and Prednisolone for Previously Untreated Stage I/II Extranodal Natural Killer/T-Cell Lymphoma, Nasal Type: A Multicenter Trial of the Korean Cancer Study Group. (3rd October 2014) - Kim, Tae Min; Kim, Dong-Wan; Kang, Yoon-Koo; Chung, Jooseop; Song, Hong-Suk; Kim, Hyo Jung; Kim, Byung Soo; Lee, Jong-Seok; Kim, Hawk; Yang, Sung Hyun; Yuh, Young Jin; Bae, Sung Hwa; et al.
Abstract: Background: Combination chemotherapy consisting of ifosfamide, methotrexate, etoposide, and prednisolone (IMEP) was active as first-line and second-line treatment for extranodal natural killer/T-cell lymphoma (NTCL). Methods: Forty-four patients with chemo-naïve stage I/II NTCL were enrolled in a prospective, multicenter, phase II study and received six cycles of IMEP (ifosfamide 1.5 g/m 2 on days 1–3; methotrextate 30 mg/m 2 on days 3 and 10; etoposide 100 mg/m 2 on days 1–3; and prednisolone 60 mg/m 2 per day on days 1–5) followed by involved field radiotherapy (IFRT). Results: Overall response rates were 73% (complete remission [CR] in 11 of 41 evaluable patients [27%]) after IMEP chemotherapy and 78% (CR 18 of 27 evaluable patients [67%]) after IMEP followed by IFRT. Neutropenia and thrombocytopenia were documented in 33 patients (75%) and 7 patients (16%), respectively. Only 8 patients (18%) experienced febrile neutropenia. Three-year progression-free survival (PFS) and overall survival (OS) were 66% and 56%, respectively. High Ki-67 (≥70%) and Ann Arbor stage II independently reduced PFS ( p = .004) and OS ( p = .001), respectively. Conclusion: Due to the high rate of progression during IMEP chemotherapy, IFRT needs to be introduced earlier. Moreover, active chemotherapy including an l -asparaginase-based regimen should be use to reduce systemic treatment failure in stage I/II NTCL.